The process of adaptation of an obese child and its relationship with maternal attitude - Castañeda Chang, Ana María (2005)
The descriptive and co-relational research shows the results obtained from a sample of 50 9 a 15-year-old children and adolescents who were diagnosed exogenous obesity and a control group of 50 children who did not present exogenous obesity, both from a school in Metropolitan Lima. A sample of mothers from both group was also considered. Significant differences in the relationship mother-children and in the process of personal adaptation between both groups were also found.